Does loneliness impact intentional weight loss? The role of obesity-related disadvantages and comorbidities - Männistö, Siniriikka A.; Joki, Anu; Suojanen, Laura-Unnukka; Venäläinen, Mikko S.; Pietiläinen, Kirsi H.; Ahola, Aila J. (Elsevier, 2026)
Objective
Loneliness is increasingly recognized as a significant factor influencing health outcomes, including weight management. Nevertheless, its role in intentional weight loss remains underexplored. The 12-month digital Healthy Weight Coaching (HWC), in Finland, offers a real-world context to investigate this relationship. We explored whether baseline loneliness affects weight loss during HWC and whether comorbidities or perceived obesity-related disadvantages mediate this relationship.
Methods
Data were included from participants enrolled in the HWC between 2016 and 2020. Baseline assessments included loneliness, comorbidities, and perceived obesity-related disadvantages. Weight was self-reported weekly, with body mass index calculated from interpolated weights at three, six, nine, and 12 months. Generalized estimating equations were used to analyze the impact of baseline loneliness on weight change, and ordinary least squares regression analyses were used to analyze mediation.
Results
Participants who felt lonely, somewhat lonely, or not lonely at baseline achieved comparable weight loss. However, higher loneliness was linked to greater perceived obesity-related disadvantages, psychological distress, number of comorbidities, and lower vitality, indirectly leading to lesser weight loss.
Conclusions
Loneliness did not directly hinder weight loss but was linked to health and psychosocial challenges that may indirectly reduce success, highlighting the need for holistic support in weight management.